Selank and semax as potential hepatoprotectors in medical treatment of tuberculosis - Alexey K. Petrovsky; Nikolay A. Smirnov; Vladimir P. Vdovichenko; Tatiana B. Fedorova; Edgar E. Kerbenev; Vladimir N. Fedorov (Belgorod National Research University, 2019)
Introduction: Drug-induced hepatitis is common in clinical practice. This problem is particularly relevant in the treatment of tuberculous infection, because for this purpose, up to 5-6 hepatotoxic drugs are used simultaneously for a long time, which often (in 15-20% of cases) leads to medical liver lesion. To protect the liver, Semax and Selank are offered - drugs of regulatory peptides group. Materials and Methods: The research was conducted on 96 outbred white male rats weighing 180-220 g. The experimental group included about 10 animals. Drug-induced hepatitis was simulated through the combined 21-day administration of isoniazid, rifampicin and ethanol. Semax and Selank, as well as Essentiale N and Mexidol (comparison drugs) were administered once a day during the experiment. Healthy control animals with experimental hepatitis were used for comparison. Subsequently, the obtained biochemical and histomorphological parameters were evaluated. Results and Discussion: In the experiment, Semax and Selank showed a greater therapeutic activity than the recognized hepatoprotectors - Essentiale and Mexidol. Only in the case of administering Selank and Semax, there was parallelism between the restoration of biochemical parameters of blood and histomorphological parameters of the liver. Selank was also characterized by an increased activity of regenerative processes. Conclusion: Administering Selank and Semax to patients with tuberculosis would significantly reduce the number and severity of hepatotoxic reactions.